Analyzing corruption, political influence, socioeconomic conditions, and living standards in Pakistan - Mazher, Dr. Muhammad Ahmad; Khan, Asma; Tramankuti, Yasotha Nair (Journal of Commerce, Management, and Tourism Studies, 2025)
The analysis examines the relationship between economic indicators and final household consumption expenditures (FHCE) in Pakistan from 1991-2023. Four variables were used: total population, corruption perception index, political stability, and absence of violence. The results show a positive association between the general population and FHCE in both the short and long terms. However, the corruption perception index reduces FHCE by 0.4430 units, with a negative short-term effect. Political stability has a moderate long-term effect. PSVA has a negative influence on FHCE. The model explains 85.60% variation in FHCE, suggesting population growth management, corruption control, and political stability policies.